Altruism in humans - Batson, C. Daniel (Charles Daniel), 1943- (Oxford : Oxford University Press, 2011)
This book takes a hard-science look at the possibility that we humans have the capacity to care for others for their sakes (altruism) rather than simply for our own (egoism). The look is based on an extensive series of theory-testing laboratory experiments conducted over the past 35 years.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: Altruism